2020
DOI: 10.1053/j.ajkd.2020.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Developing Consensus-Based Outcome Domains for Trials in Children and Adolescents With CKD: An International Delphi Survey

Abstract: The inconsistency in outcomes reported and lack of patient-reported outcomes across trials in children with chronic kidney disease (CKD) limits shared decision making. As part of the Standardized Outcomes in Nephrology (SONG)-Kids initiative, we aimed to generate a consensus-based prioritized list of critically important outcomes to be reported in all trials in children with CKD. Study Design: An online 2-round Delphi survey in English, French, and Hindi languages. Settings & Participants: Patients (aged 8-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…16 For children with CKD, meaningful activities include study, sport, social and leisure activities. 17 18 Life participation is often restricted by the symptoms, side effects and treatment burden associated with CKD, and this has long-term consequences in young adulthood. 7 8 19 20 …”
Section: Introductionmentioning
confidence: 99%
“…16 For children with CKD, meaningful activities include study, sport, social and leisure activities. 17 18 Life participation is often restricted by the symptoms, side effects and treatment burden associated with CKD, and this has long-term consequences in young adulthood. 7 8 19 20 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the Likert scale, the final round of the survey will include a Best Worst Scale (BWS), a type of discrete choice experiment which allows participants to assess the relative importance of each outcome [ 39 ]. The BWS methodology has been used in previous SONG Delphi surveys [ 20 , 34 , 35 ] and has also been used to assess patient preferences in kidney transplantation [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adjusting clinical research to include patient-focused outcomes is foundational to understanding the needs and hopes of patients and families across disease, cultural, and developmental states. 79,[84][85][86] Additionally, there is a need to develop and study targeted interventions focused upon patient-reported and prioritized outcomes including symptoms present in CKD, such as pain, pruritis, edema, and sleep disturbances. Finally, effective models for routine integration of PPC into clinical care for children with CKD must be developed, applied and investigated.…”
Section: Directions For Future Opportunities To Integrate Ppc Into Pediatric Nephrologymentioning
confidence: 99%